Pilot Study on Assess the Effectiveness of Life Skill Training Program on Social Adjustment among Adolescents - Saravanan S; Tamizharasi K (International Journal of Nursing Research, 2024)
Background: The adolescent stage represents the pinnacle of intellectual, physical, social, emotional, and all other developmental capacities. Adolescents require specific skills to adapt to society and deal with the rapid development. Life skills may fill the gap and support the holistic development of adolescents. The present study is designed to find the effectiveness of life skill training on social adjustment among adolescents. Methods: Quantitative experimental research study was adopted for the study. Fifteen–18-year-old adolescents studying 11th and 12th standard were selected randomly from the higher secondary schools. Dr. Ashutosh Kumar’s, social adjustment scale was used for the measurement. Five–60-min sessions of life skill training were given to experimental group on weekly basis. Results: The findings reveal that in experimental group, the pre-test and post-test mean score of social adjustment was 62.85 ± 5.23 and 65.88 ± 5.38, respectively. The calculated “t” value was 4.89 which was greater than the table value. In post-test experimental and control group, the mean score was 65.88 ± 5.38 and 59.88 ± 7.93, respectively. The calculated “t” value was 3.70 which was greater than the table value. Thus, it becomes evident that the life skill training program was effective in improving social adjustment. Conclusion: The study concluded that the training program was worth in implanting to adolescents group and recommends to do further research on the training to measure more variables including emotional aspects.